Maternal temperament and character: associations to child behavior at the age of 3 years - Sara Agnafors; Marie Bladh; Lisa Ekselius; Carl Göran Svedin; Gunilla Sydsjö (BMC, 2021)
Abstract Background The influence of maternal temperament on child behavior, and whether maternal temperament impact boys and girls differently is not thoroughly studied. The aim was to investigate the impact of maternal temperament and character on child externalizing and internalizing problems at age 3. Methods A birth-cohort of 1723 mothers and their children were followed from birth to age 3. At the child's age of 3 months, the mothers filled out standardized instruments on their temperament and character using the Temperament and Character Inventory (TCI) and depressive symptoms using the Edinburgh Postnatal Depression Scale (EPDS). At the child's age of 3 years, the mothers reported on child behavior using the Child Behaviour Checklist (CBCL). Results Maternal temperamental trait novelty seeking was positively associated with externalizing problems in the total population and in girls. Harm avoidance was positively associated with externalizing problems in the total population and in boys, and with internalizing problems in the total population and boys and girls respectively. Maternal character traits of self-directedness and cooperativeness were negatively associated with both externalizing and internalizing problems in the total population and in boys and girls respectively. Conclusions Maternal character traits were more influential on child behavior than were temperamental traits, and thus the opportunities for intervention targeted at parental support are good. Maternal mental health and socioeconomic aspects also increased the risk for child behavior problems, indicating the need for recognition and support in clinical settings.